Development of Power Point-Based Mathematics Learning Media on Systems of Linear Equations with Three Variables - Nurhaliza, Siti (EDUCTUM: Journal Research, 2023)
In media education functions as a means or tool to achieve learning goals. Because the information contained in the media must be able to involve participants students both in mind or mentally and in the form of real activities, so that learning can occur. One of the mathematical materials that requires the use of media is material on three-variable linear equation systems and the most frequently used media educators use Microsoft Powerpoint media because this media is easy to understand, therefore it is necessary to develop a media PowerPoint-based learning because it is through learning media Powerpoint can increase student participation over time more meaningful and so that students become more enthusiastic during the process learning and the learning objectives to be achieved are achieved well.